2011
DOI: 10.1016/j.bbamem.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Human cells and cell membrane molecular models are affected in vitro by the nonsteroidal anti-inflammatory drug ibuprofen

Abstract: This report presents evidence that ibuprofen interacts with red cell membranes as follows: a) in scanning electron microscopy (SEM) studies on human erythrocytes induced shape changes at a concentration as low as 10μM; b) in isolated unsealed human erythrocyte membranes (IUM) induced mild increase in the water content or in their molecular dynamics at the hydrophobic-hydrophilic interphase, while a corresponding ordering decrease at the deep phospholipids acyl chain level; c) at physiological temperature (37°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…These drugs also decreased the main transition temperature of DMPC bilayers and induced a broadening effect on the transition. 52 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 structure of CZX exhibits hydrophobic nature. This inference also agrees with the computer simulation result indicating that the location of CZX molecules in dioleoyl-PC bilayers is around the interface between the hydrophilic and hydrophobic parts of the bilayer membrane.…”
Section: Bilayer Structure Modelingmentioning
confidence: 95%
“…These drugs also decreased the main transition temperature of DMPC bilayers and induced a broadening effect on the transition. 52 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 structure of CZX exhibits hydrophobic nature. This inference also agrees with the computer simulation result indicating that the location of CZX molecules in dioleoyl-PC bilayers is around the interface between the hydrophilic and hydrophobic parts of the bilayer membrane.…”
Section: Bilayer Structure Modelingmentioning
confidence: 95%
“…31 Manrique-Moreno et al also analyzed the behavior of IBU in human erythrocytes and in red cell membrane models, combining DSC with other techniques such as X-ray diffraction and scanning electron microscopy. 33 Their experimental data suggested that this NSAID interacts with lipid bilayers and the erythrocyte membrane, affecting the morphology of the latter at concentrations lower than the therapeutic and toxic plasma levels. In particular, DSC experiments showed that IBU reduced the cooperativity between the PL molecules.…”
Section: Investigating the Toxicity Of Nsaidsmentioning
confidence: 98%
“…These guide the microenvironment of the membrane interior and surface that in turn are expected to modulate the drug-membrane interaction. Ibuprofen interacts with red cell membranes and changes their shapes at a very low concentration (as low as 10 M) [148]. and other chemical groups (nimesulide, indomethacin, ibuprofen, etc.)…”
Section: Consequences Of Nsaid Membrane Interaction: Perturbation/flumentioning
confidence: 99%